Turmeric Extract Bioindicator in Identification of Borax Compounds in Meatballs - Firmansyah, Dodiy; Pramajati, Gilang; Sumiatun, Sumiatun; Sarlita Kartiani, Baiq (JUPE : Jurnal Pendidikan Mandala, 2024)
Meatballs are food made from beef, chicken, fish and shrimp, which are popular with people, from children to adults. In managing meatballs, food additives (BTP) are often added which can make the meatballs chewier and last longer, thereby inhibiting the growth of microorganisms caused by the borax content. Borax is a substance that is often used as a preservative and improves the texture of foods such as meatballs, however the use of borax as a food preservative is prohibited in Indonesia because it can cause various diseases such as central nervous disorders and liver problems. This research is to determine whether or not there is Borax in Meatballs that are bought and sold around Praya City, Central Lombok Regency by using a sampling method from 5 meatball stalls, from samples that have been qualitatively tested, several samples have borax content which was tested using turmeric extract, showing that the color change in the meatball samples that had been dripped with turmeric extract contained 3 negative control meatball samples (-) A, C, D, and 2 positive controls (+) B and E, while the 2 positive (+) meatball samples were tested using borax FT-IR to detect OH groups (Hydroxyl) C=C bonds and C-H bonds are found in the Spectra.